Pure bone-borne palatal expander anchored on orthodontic mini-implants Micro-4 or Micro-6 Expander - Winsauer, Heinz; Walter, Andre; Jaeschke, Doreen; Winsauer, Clemens; Muchitsch, Alfred; Wendl, Brigitte (Journal of Stomatology, 2015)
Introduction. Orthodontic treatment of patients with narrow maxilla is usually done with tooth- borne expanders and in relation to age as surgically assisted maxillary expansion (SAME). Dental side effects are commonly seen. The routine and safe use of orthodontic mini-implants (OMI) in the anterior palate has encouraged the use of the so-called hybrid expanders, which are partially bone-borne and partially tooth-borne. Investigations of the bone depth and bone density in the anterior palate show that a bilateral area of sufficient bone depth (“footprint scheme“) is a secure region for placing 2 to 3 OMIs per side. A double telescopic expansion screw (Super screw) bonded with collars to the OMI heads proved to be a reliable, stable and still easy to remove pure bone-borne maxillary expander (MICRO-4 or MICRO-6 expander). Methods. This article describes the maxillary expansion with MICRO4 of a female, aged 14.6 years with bilateral head bite and lingually tipped lower buccal teeth (C1), a female, aged 15.0 years with bilateral crossbite (C2), a male, aged 21 years with a narrow maxilla and bilateral crossbite (C3). In all cases four OMIs (Jet screw: length 12-14Introduction. Orthodontic treatment of patients with narrow maxilla is usually done with tooth- borne expanders and in relation to age as surgically assisted maxillary expansion (SAME). Dental side effects are commonly seen. The routine and safe use of orthodontic mini-implants (OMI) in the anterior palate has encouraged the use of the so-called hybrid expanders, which are partially bone-borne and partially tooth-borne. Investigations of the bone depth and bone density in the anterior palate show that a bilateral area of sufficient bone depth (“footprint scheme“) is a secure region for placing 2 to 3 OMIs per side. A double telescopic expansion screw (Super screw) bonded with collars to the OMI heads proved to be a reliable, stable and still easy to remove pure bone-borne maxillary expander (MICRO-4 or MICRO-6 expander). Methods. This article describes the maxillary expansion with MICRO4 of a female, aged 14.6 years with bilateral head bite and lingually tipped lower buccal teeth (C1), a female, aged 15.0 years with bilateral crossbite (C2), a male, aged 21 years with a narrow maxilla and bilateral crossbite (C3). In all cases four OMIs (Jet screw: length 12-14 mm, diameter 2.5 mm, Jeil Medical, South Korea) were used to support the expander. Other details like the temporary closure of the diastema, the bonding and the removal of the appliance and the insertion of a collar bonded TPA are explained. Results. All presented cases were expanded without surgical assistance. The amount of expansion in C1 was 5.8 mm, in C2 9.0 mm and in C3 16.0 mm. All head and cross bites were corrected and additionally, in C1, the lower buccal teeth were uprighted. Biomechanical considerations, clinical efficacy, and the advantages and potential complications of pure OMI-borne expansion treatment are discussed. Conclusions. These case reports illustrate the use of MICRO-4 expanders to widen the maxilla providing an efficient approach for the treatment of patients with partially severe transverse deficiency without dental side effects. The MICO-4 expander is a minimally invasive, reliable, stable and high patient comfort appliance and for this reason, palatal expansion is enabled in more adult patients without surgical assistance.